Empirical relations to estimate underwater PAR attenuation in San Quintín Bay using Secchi depth and horizontal sighting range - Montes-Hugo, MA (Iniversidad Autónoma de Baja California, 2005)
Empirical relationships to estimate vertical attenuation coefficient of photosynthetically available radiation (KPAR) using Secchi disk, vertical black disk, and horizontal sighting ranges for San Quintín Bay, Baja California, were developed. Radiometric PAR profiles were used to calculate KPAR. Vertical (ZD) and horizontal (HS) sighting ranges were measured with white (Secchi depth or ZSD, HSW) and black (ZBD, HSB) targets. The empirical power models KPAR = 1.48 ZSD–1.16, KPAR = 0.87 ZBD–1.52, KPAR = 0.54 HSW–0.65 and KPAR = 0.53 HSB–0.92 were developed for the corresponding relationships. The parameters of these models are not significantly different from those of models developed for Punta Banda Estuary, another Baja California lagoon, with the exception of the one for the KPAR-HSW relationship. Also, parameters of the KPAR-ZSD model for San Quintín Bay and Punta Banda Estuary are not significantly different from those developed for coastal waters near Santa Barbara, California. A set of general models is proposed that may apply to coastal water bodies of northwestern Baja California and southern California (KPAR = 1.45 ZSD –1.10, KPAR = 0.92 ZBD–1.45, and KPAR = 0.70 HSB –1.10). While this approach may be universal, more data are needed to explore the variability of the parameters between different water bodies.